Analisis Bauran Promosi Dalam Meningkatkan Minat Pembelian Di Hidden Gem Lengkong Alit - Prima Wardana, Asep; Nadiyanto Prastian, Angga (Jurnal Online Manajemen ELPEI, 2025)
Hidden Gem Lengkong Alit has implemented a good Promotion Mix in increasing purchasing interest. It is known that advertising and publications contribute to increasing awareness of the location and products at Hidden Gem Lengkong Alit, while sales promotions through food bloggers and word of mouth methods contribute to increasing customer purchasing interest. Direct marketing by Business Actors helps in direct interaction by offering attractive discounts in an effort to increase purchasing interest. Evaluations that have been carried out by Business Actors at Hidden Gem Lengkong Alit include improving products and services and optimizing promotional strategies that have been implemented by Business Actors at Lengkong Alit. This study tells culinary business actors how to optimize their promotional mix to increase purchasing interest and competitiveness as well as business sustainability at Hidden Gem Lengkong Alit.